A warp-speed method for conducting Monte Carlo experiments involving bootstrap estimators - Raffaella Giacomini; Dimitris Politis; Halbert White (Centre for Microdata Methods and Practice (cemmap), 2012)
We analyze fast procedures for conducting Monte Carlo experiments involving bootstrap estimators, providing formal results establishing the properties of these methods under general conditions.
Keywords: 330